2018
DOI: 10.1177/1557988318804725
|View full text |Cite
|
Sign up to set email alerts
|

Father 2 Son: The Impact of African American Father–Son Sexual Communication on African American Adolescent Sons’ Sexual Behaviors

Abstract: Parent–child sexual communication has been associated with reducing adolescent sexual risk behaviors. Limited research on parent–child sexual communication has been conducted on African American (AA) adolescent males who are at increased risk of sexually transmitted infections (STIs) including HIV/AIDS. The purpose of this research was to examine AA father–son sexual communication and the effect of contextual factors on the sexual risk behaviors. The final sample consisted of 96 AA adolescent males, ages 16–21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 83 publications
(107 reference statements)
1
23
0
2
Order By: Relevance
“…In addition, AA sons' permissiveness positively predicted their sexual behaviors. This is important, despite the limited research, as father-child sexual communication and other relational factors may be important in helping increase the HIV testing uptake of AA adolescents (Harris et al, 2019). The influence of AA father-adolescent sexual communication on HIV prevention uptake constitutes a significant gap in the literature.…”
mentioning
confidence: 99%
“…In addition, AA sons' permissiveness positively predicted their sexual behaviors. This is important, despite the limited research, as father-child sexual communication and other relational factors may be important in helping increase the HIV testing uptake of AA adolescents (Harris et al, 2019). The influence of AA father-adolescent sexual communication on HIV prevention uptake constitutes a significant gap in the literature.…”
mentioning
confidence: 99%
“…The studies using self-administered questionnaires reported relatively higher proportions of the primary and secondary sexual abstinence. The range of the proportions of secondary sexual abstinence widened with increased duration of sexual abstinence, being lowest for 1 month (4.6%e 50.3%), 27,38,40,43 followed by 6e8 months (7.1%e 60.1%) 35,36,44 and 1 year (0%e83.6%). 4,7,10,13,16,23,28,31,32,34,37 Factors in Sexual Abstinence…”
Section: Secondary Sexual Abstinencementioning
confidence: 99%
“…Furthermore, age categorization in the selected studies showed that the prevalence of secondary sexual abstinence for 10-to 19year-old men ranged from 1.3% to 83.6%, 4,7,9,13,16,29 while for 15-to 24-year-old men, it ranged from 10.2% to 50.3%. 8,13,16,23,31,32,34,40,43 Based on the age categories given in the selected studies, the prevalence of secondary sexual abstinence was 0%e50.3% for men from 18 to 30 years old, 9,15,40,43,44…”
Section: Primary Sexual Abstinencementioning
confidence: 99%
“…Research also suggests that gender differences exist in relation to the impact of parent-child communication about sex on sexual behaviour and outcomes, with impacts emerging as more significant following motherchild than father-child communication [30]. A recent study exploring father-son communication among African Americans, however, demonstrated that father-son communication is an important factor in decreasing adolescent males' sexual risk behaviours and HIV risk [58].…”
Section: Gender Differences In Intergenerational Communication About Sexmentioning
confidence: 99%
“…If we get good quality training for all staff, not just a few key teachers, then staff will be more comfortable teaching it. is important to be mindful that adolescents will not always have same-sex preferences in relation to parent communication about sex [54], given the important role that male caregivers might play in RSE [58,84] and young men's expressed desire for their fathers to provide them with information about sex [54], this is an important area for further research.…”
Section: Implementation Fidelitymentioning
confidence: 99%